Culture-Negative Endocarditis Diagnosed Using 16S DNA Polymerase Chain Reaction - Stephen Duffett; Bayan Missaghi; Peter Daley (Canadian Journal of Infectious Diseases and Medical Microbiology)
16S DNA polymerase chain reaction (PCR) is a molecular amplification technique that can be used to identify bacterial pathogens in culture-negative endocarditis. Bacterial DNA can be isolated from surgically excised valve tissue or from blood collected in EDTA vials. Use of this technique is particularly helpful in identifying the bacterial pathogen in cases of culture-negative endocarditis. A case involving a 48-year-old man who presented with severe aortic regurgitation and a four-month prodrome of low-grade fever is reported. Blood and valve tissue cultures following valve replacement were negative. A valve tissue sample was sent for investigation with 16S DNA PCR, which successfully identified Streptococcus salivarius and was interpreted as the true diagnosis. A review of the literature suggests that 16S DNA PCR from valve tissue is a more sensitive diagnostic test than culture. It is also extremely specific, based on a sequence match of at least 500 base pairs.